Centralized management of Soviet town planning. 1931–1937 - Kosenkova, Julia (project baikal, 2021)
In the 1930s, as industrialization gathered pace, great hopes were laid on the centralized management of town planning as opposed to the assertiveness of large industrial institutions. In that period, the All-Union Council of Utility Services of the USSR Central Executive Committee had the highest status. Studying new materials deposited in the RF State Archives, the author revealed that even the all-union management structure regularly experienced difficulties which paralyzed its urban planning and reconstruction activities.
Keywords: history of town planning in the Soviet period; planning of cities and industrial areas; town-planning activity; municipal economy